Geographical information: A practical approach - Zhu, Xuan (London Routledge, 2025)
This textbook provides the fullest available introduction to GIS and their environmental, social and economic applications. This new edition has been substantially revised and updated to incorporate the key developments in GIS technology and spatial data science and their applications that have taken place in recent years